Modern methods of design and analysis of optical systems on example of the off-axis catadioptric system - Murzakulov, G.; Nurguzhin, M.; Albazarov, B.; Zhumazhanov, B. (Recent Contributions to Physics, 2013)
The article is devoted to design and analysis technology of parameters of the telescope used on small satellites for remote sensing purposes. Software products used for optical systems design are listed and some their capabilities are described. The main design phases for remote sensing telescope are described on the example of catadioptric system and necessity of those phases is shown. The factors which lay on the base of choosing telescope parameters are shown. Some results of analysis of the optical system are presented, so it is possible to make initial estimations of the system capabilities. On the basis of computations of the system tolerance to manufacture and assembly errors and to environment conditions changes, the way of computation of mechanical margins at manufacture of system elements is described. The applied model philosophy is given, verification phase is described. The article is based on the work done by the specialists of the JSC «National company «Kazakhstan Gharysh sapary» in frames of the project «Creation of the remote sensing space system of republic of Kazakhstan». The works are done in collaboration with the specialists of companies EADS Astrium (France) and SSTL (Great Britain). The article presents the general view of modern methods of developing optical payloads for small satellites.